Efficacy and safety of calcium, magnesium, potassium, and sodium oxybates (lower-sodium oxybate [LXB]; JZP-258) in a placebo-controlled, double-blind, randomized withdrawal study in adults with narcolepsy with cataplexy - Bogan, Richard K; Thorpy, Michael J; Dauvilliers, Yves; Partinen, Markku; Del Rio Villegas, Rafael; Foldvary-Schaefer, Nancy; Skowronski, Roman; Tang, Lihua; Skobieranda, Franck; Šonka, Karel (Sleep, 2021)
STUDY OBJECTIVES: Evaluate efficacy and safety of lower-sodium oxybate (LXB), a novel oxybate medication with 92% less sodium than sodium oxybate (SXB). METHODS: Adults aged 18-70 years with narcolepsy with cataplexy were eligible. The study included a ≤30-day screening period; a 12-week, open-label, optimized treatment and titration period to transition to LXB from previous medications for the treatment of cataplexy; a 2-week stable-dose period (SDP); a 2-week, double-blind, randomized withdrawal period (DBRWP); and a 2-week safety follow-up. During DBRWP, participants were randomized 1:1 to placebo or to continue LXB treatment. RESULTS: Efficacy was assessed in 134 participants who received randomized treatment, and safety was assessed in all enrolled participants (N = 201). Statistically significant worsening of symptoms was observed in participants randomized to placebo, with median (first quartile [Q1], third quartile [Q3]) change in weekly number of cataplexy attacks from SDP to DBRWP (primary efficacy endpoint) in the placebo group of 2.35 (0.00, 11.61) versus 0.00 (-0.49, 1.75) in the LXB group (p < 0.0001; mean [standard deviation, SD] change: 11.46 [24.751] vs 0.12 [5.772]), and median (Q1, Q3) change in Epworth Sleepiness Scale score (key secondary efficacy endpoint) of 2.0 (0.0, 5.0) in the placebo group versus 0.0 (-1.0, 1.0) in the LXB group (p < 0.0001; mean [SD] change: 3.0 [4.68] vs 0.0 [2.90]). The most common treatment-emergent adverse events with LXB were headache (20.4%), nausea (12.9%), and dizziness (10.4%). CONCLUSIONS: Efficacy of LXB for the treatment of cataplexy and excessive daytime sleepiness was demonstrated. The safety profile of LXB was consistent with SXB. CLINICAL TRIAL REGISTRATION: NCT03030599.
Keywords: Magnesium; dospělí; draslík; hořčík; Sodium; Potassium; Adult; výsledek terapie; mladý dospělý; Adolescent; lidé; dvojitá slepá metoda; cataplexy; Cataplexy; Treatment Outcome; vápník; excessive daytime sleepiness; JZP-258; kataplexie; Sodium Oxybate; Double-Blind Method; Calcium; sodík; Aged; Young Adult; narcolepsy; narkolepsie; Narcolepsy; sodium oxybate; lidé středního věku; senioři; oxybát sodný; Middle Aged; mladiství; Humans